2022
DOI: 10.1038/s41541-022-00551-4
|View full text |Cite
|
Sign up to set email alerts
|

Immune correlates of protection following Rift Valley fever virus vaccination

Abstract: Rift Valley fever virus (RVFV) is a hemorrhagic fever virus with the potential for significant economic and public health impact. Vaccination with an attenuated strain, DelNSsRVFV, provides protection from an otherwise lethal RVFV challenge, but mechanistic determinants of protection are undefined. In this study, a murine model was used to assess the contributions of humoral and cellular immunity to DelNSsRVFV-mediated protection. Vaccinated mice depleted of T cells were protected against subsequent challenge,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Hu-PBL models have the advantage of faithfully mimicking the so-called patient memory immune response in the mouse. In particular, it was demonstrated that the hu-PBL/DC model enables the investigation of correlates of immunity in EVD survivors [ 43 ], which might be expanded to the investigation of other viral infections, such as infection with Rift Valley fever virus (RVFV) [ 116 ], SARS-CoV-2 infection and reinfection [ 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ], or yellow fever virus (YFV) infection [ 127 ]. In this way, it is also possible to analyze the interactions that take place between the immune cells throughout the development of a specific disease given that they have been demonstrated to enable the sequential engraftment of distinct cell types [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hu-PBL models have the advantage of faithfully mimicking the so-called patient memory immune response in the mouse. In particular, it was demonstrated that the hu-PBL/DC model enables the investigation of correlates of immunity in EVD survivors [ 43 ], which might be expanded to the investigation of other viral infections, such as infection with Rift Valley fever virus (RVFV) [ 116 ], SARS-CoV-2 infection and reinfection [ 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ], or yellow fever virus (YFV) infection [ 127 ]. In this way, it is also possible to analyze the interactions that take place between the immune cells throughout the development of a specific disease given that they have been demonstrated to enable the sequential engraftment of distinct cell types [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…For RVFV, the virus neutralization test based on a virulent virus is considered a gold standard for the detection of neutralizing antibodies; however, progress is being made with neutralization tests using attenuated strains, virus-like particles or pseudotyped virus particles that can be performed under BSL-2 conditions [ 77 ]. In humans, clear T-cell-based correlates of protection have yet to be described, though a recent study indicated a clear role for cellular immunity in protection through the interaction of various cellular components [ 78 ]. The concept for any RVF vaccine to differentiate naturally infected from vaccinated individuals or animals (e.g., DIVA) is a diagnostic challenge that may best be assessed as a part of large-scale clinical trials.…”
Section: Beyond Proof-of-concept Challengesmentioning
confidence: 99%
“…The protective capacity of neutralizing antibodies has been demonstrated through passive transfer of convalescent sera to susceptible animals 1,38 . Furthermore, data from vaccine studies have demonstrated that high serum‐neutralizing titers are sufficient to provide protection in animal challenge models 40 . Study of individuals exposed to RVFV occupationally has shown that naturally acquired immunity can be long‐lived, with neutralizing antibodies being readily detectable despite a lack of additional virus exposures 41–43 .…”
Section: Humoral Immune Response To Phlebovirus Infectionmentioning
confidence: 99%
“…Study of individuals exposed to RVFV occupationally has shown that naturally acquired immunity can be long‐lived, with neutralizing antibodies being readily detectable despite a lack of additional virus exposures 41–43 . Immune correlates of protection against RVFV have been studied in mice vaccinated with an RVFV attenuated vaccine (DelNSsRVFV) 40 . Mice were protected from lethal RVFV challenge with or without depletion of CD4 + and/or CD8 + T cells, or B cells prior to RVFV challenge.…”
Section: Humoral Immune Response To Phlebovirus Infectionmentioning
confidence: 99%
See 1 more Smart Citation